Profil Motivasi Belajar Peserta Didik Kelas VIII di SMP Sima Padang - Isnawati, Fifit (Lembaga Riset Mutiara Akbar, 2022)
This research is motivated by the presence of students whose learning motivation tends to be low, there are students who tend not to focus when studying and play mobile phones more often, there are students who pay less attention when the teacher teaches in class. The purpose of this study was to describe the learning motivation profile of class VIII students at SMP SIMA Padang seen from: 1) Students' learning motivation was seen from intrinsic motivation. 2) Students' learning motivation was seen from extrinsic motivation. This research was conducted using quantitative descriptive methods. The study population was 141 students who were selected by proportional random sampling technique with 59 participants. The instrument used is a questionnaire. Meanwhile, for data analysis using percentage classification. Based on the results of research on the learning motivation profile of class VIII students at SMP SIMA Padang seen from: 1) Students' learning motivation seen from intrinsic motivation is in the fairly good category 2) Students' learning motivation seen from extrinsic motivation is in the fairly good category. This research is recommended to students in order to increase their learning motivation